2015
DOI: 10.1111/cas.12715
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in development, metastasis and drug resistance of breast cancer

Abstract: Transport through the cell membrane can be divided into active, passive and vesicular types (exosomes). Exosomes are nano-sized vesicles released by a variety of cells. Emerging evidence shows that exosomes play a critical role in cancers. Exosomes mediate communication between stroma and cancer cells through the transfer of nucleic acid and proteins. It is demonstrated that the contents and the quantity of exosomes will change after occurrence of cancers. Over the last decade, growing attention has been paid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 69 publications
(134 reference statements)
0
140
0
1
Order By: Relevance
“…Tumor heterogeneity and resistance to therapy may occur from MV-mediated transfer of genetic material between cells [13]. Thus, the characterization of this phenomenon could have important clinical ramifications most notably in the development of new therapeutically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor heterogeneity and resistance to therapy may occur from MV-mediated transfer of genetic material between cells [13]. Thus, the characterization of this phenomenon could have important clinical ramifications most notably in the development of new therapeutically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst exosomes provide effective tools for transportation of anti-cancer drugs with lower toxicity [51], it is important to consider their function as immuno-stimulating or immuno-suppressing moieties [52]. Exosomes have been proposed to play a role in shaping the tumor microenvironment through their involvement in various biological processes including angiogenesis, immune escape, and triggering an epithelial-to- mesenchymal transition (EMT) leading to metastasis initiation [53].…”
Section: Strategies For Therapeutic Deployment Of Exosomesmentioning
confidence: 99%
“…Exosomes have been reported to be involved in all stages in cancer development: (i) tumorigenic transformation, (ii) tumor growth, (iii) angiogenesis, (iv) modulation of immune responses, and (v) induction of mechanisms to acquire therapy resistance. [50][51][52][53] The impact of exosomes in clinical research is demonstrated by the fact that there are already 19 clinical trials ongoing (web site https://clinicaltrials.gov/). Among them, 13 involve the study of exosomes as cancer diagnosis biomarkers whereas the others use the exosomes for cancer therapy purposes.…”
Section: Clinical Interest Of Exosomes In Cancermentioning
confidence: 99%